A year in the life of ancient Egypt - David, A. Rosalie (Pen & Sword Archaeology, 2015)
AFRICAN HISTORY : BCE TO C 500 CE. Based on years of prestigious academic work, Professor Rosalie David cleverly presents every aspect of life in ancient Egypt through the lives of various characters, all based on mummies from the Manchester Museum of whom Professor Rosalie David has led the study. Characters hail from all walks of life, including royalty, nobles, officials, craftsmen and peasants, allowing us an insight into absolutely every aspect of everyday, ritual and religious life in ancient Egypt. The book provides an overview of the many dynasties and kingdoms of ancient Egypt before beginning to tell the story of the lives of one family. All three seasons of inundation, planting and growing, and harvesting are covered as well as all ritual and religious events, including birth and death.